2018
DOI: 10.1038/s41467-018-06222-0
|View full text |Cite
|
Sign up to set email alerts
|

Single cell molecular alterations reveal target cells and pathways of concussive brain injury

Abstract: The complex neuropathology of traumatic brain injury (TBI) is difficult to dissect, given the convoluted cytoarchitecture of affected brain regions such as the hippocampus. Hippocampal dysfunction during TBI results in cognitive decline that may escalate to other neurological disorders, the molecular basis of which is hidden in the genomic programs of individual cells. Using the unbiased single cell sequencing method Drop-seq, we report that concussive TBI affects previously undefined cell populations, in addi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
156
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(174 citation statements)
references
References 62 publications
12
156
3
3
Order By: Relevance
“…45 ), MGP 46 ), choroid cells (LCN2 (ref. 47 ), 1500015O10Rik 48 ), endothelial cells (ITM2A 49 , FLT1 (ref. 50 )), GABAergic neuron (NPY 51 , NR2F2 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…45 ), MGP 46 ), choroid cells (LCN2 (ref. 47 ), 1500015O10Rik 48 ), endothelial cells (ITM2A 49 , FLT1 (ref. 50 )), GABAergic neuron (NPY 51 , NR2F2 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…To study the dynamics of Wnt signaling both in the mesenchyme and in the epithelium, we cultured E60 mandible slices for 12 and 24 h and compared β‐catenin expression levels between the nucleus and cytoplasm among the E60 (cultured for 0 h), E90, E60 (cultured for 12 h), and E60 (cultured for 24 h) groups via an RNAscope assay—an RNA ISH technique for single‐molecule detection that can identify the subcellular location of signal (i.e., in the nucleus and cytoplasm) (Arneson et al , ; Schulz et al , ). Quantification results indicated that during PC initiation from E60 to E90, the nuclear β‐catenin signal of the mesenchyme decreased approximately 10‐fold, while the nuclear β‐catenin signal of the epithelium increased approximately threefold.…”
Section: Resultsmentioning
confidence: 99%
“…Recent scRNA seq technologies have made it possible to study transcriptional 71 differences in each cell-type in healthy and diseased brains, as well as in brain injuries such as 72 traumatic brain injury (Keren-Shaul, Spinrad et al 2017, Arneson, Zhang et al 2018, Batiuk,73 Martirosyan et al 2020). In this study, we were interested in the transcriptional changes that 74 occur after astrocyte-specific activation using the Gq-DREADD.…”
Section: Introduction 44mentioning
confidence: 99%